2022
DOI: 10.3390/app13010085
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Delay Time on Rock Fragmentation in Bench Blasting

Abstract: Delay time is an important factor in the quality of bench blasting. The development and application of electronic detonators make it possible to control the timing of detonation by a highly precise delay time. It is an easily achievable way to seek a better blast fragmentation by controlling the delay time. In order to investigate the influence of delay time on rock fragmentation, eight experiments on bench blasting models with double holes were carried out. The average weight of 4.59 g of pentaerythritol tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Each end of the tube was wrapped with black tape to form a lining equal to the diameter of the borehole to make sure the explosive column was positioned at the center of the borehole. In order to provide accurate delayed initiation between boreholes, the initiation timing of the explosive columns in the boreholes was controlled by changing the length of detonating cord, referring to the detonation method used in previous studies [27,30]. According to the information from the supplier, the detonating cord had a linear density of 4.25 g/m and a detonation velocity of 6850 m/s.…”
Section: Specimen and Explosivementioning
confidence: 99%
See 1 more Smart Citation
“…Each end of the tube was wrapped with black tape to form a lining equal to the diameter of the borehole to make sure the explosive column was positioned at the center of the borehole. In order to provide accurate delayed initiation between boreholes, the initiation timing of the explosive columns in the boreholes was controlled by changing the length of detonating cord, referring to the detonation method used in previous studies [27,30]. According to the information from the supplier, the detonating cord had a linear density of 4.25 g/m and a detonation velocity of 6850 m/s.…”
Section: Specimen and Explosivementioning
confidence: 99%
“…Their results indicated that the best fragmentation could be obtained by detonating the second blast hole when the damage process of the first blast hole reached its final state. Tang et al [30] used double-hole bench specimens to study the influence of delay time on rock fragmentation. Their study indicated that a long delay without stress wave superposition obtained the best blasting excavation quality.…”
Section: Introductionmentioning
confidence: 99%
“…[5] performed drop test to study the material grindability on three granites, comparing specimens blasted and not blasted; in conclusion blasting appears to reduce the work index by 5-11%. [6] conducted eight experiments on granite bench blasting models employing double holes with delay times ranging from approximately 13 ms to 300 ms, finding an "optimal" inter-hole delay at 200 µs, where to simultaneous detonation, the median size was decreased by about 14.5% for the inter-hole delay of 200 µs; the same authors in [7] conducted a similar test and found that, compared to short delay times such as 27.36 µs, x50 was improved by approximately 25% at the delay time of 180 µs. The results indicated a notable difference and substantial improvement in fragmentation when the delay times fell within the range of no-shock-wave interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the influence of delay time on rock fragmentation, Tang et al [8] conducted eight experiments employing bench blasting models with double holes. The results reported a significant difference and great improvement in fragmentation when the delay times were in the range of a no shock wave interaction compared to other interactions.…”
Section: Introductionmentioning
confidence: 99%